PENERAPAN MODEL PEMBELAJARAN TIPE GI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 030 SIBUAK - ginting, Rehulina; Marhadi, Hendri; ', Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the problem in this research was IPS learning outcomes in fifth grade (v) students SDN 030 Sibuak still low with average value 64.50 (with KKM  70). The purpose of this research was to improve IPS learning outcomes of the fifth grade (v) students SDN 030 Sibuak with the implementation of cooperatif’s GI tipe learing model. This research was classroom action research with two cycles. The subjects were students  of class v SDN 030 Sibuak academic years 2015/2016 which amounted 15 people consisting of 5 women and 10 men. Based on the result a discussion the observation of teacher ‘s and student activity sheet seen rising each meeting. Teacher ‘s activity with the implementation of cooperatif ‘s GI tipe learning model at first meeting of first ceyle was  54.16 % (good), and second meeting was  62.50%( enough). At  second cycle, teacher ‘s activity at first meeting was 70.80% (good) and second meeting was  75.00%( good). Students activities at first meeting of first cycle was  50.00% (enough) and second meeting was 65.00% ( enough)  at second cycle, students activities at  first meeting was70.00% (good), secoond meeting was 85.00% (good), IPS learning outcomes before implementation cooperatif ‘s GI tipe learing model average 64.50, after implementation of cooperatif’ s GI tipe learing model UH I was 80.00, UH II 89.60. implementation of cooperatif’ s GI tipe learing modei can improved IPS learing outcomen of the fifth grade(V) students SDN 030 Sibuak Key Words: Cooperatif’s Group Investigation Tipe Learning Model, IPS Studies Students Achievement